2013
DOI: 10.4321/s1135-57272013000300009
|View full text |Cite
|
Sign up to set email alerts
|

Efecto del consumo de una harina de maíz enriquecida con soja en el estado de nutrición de mujeres indígenas de México

Abstract: enriched flour is an ideal food for marginalized women in rural areas who are underweight, are undernourished and have anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…One RCT found that six months after the fortification of maize flour, women who consumed the fortified flour had a significant increase in hemoglobin concentrations (mean 13.3 g/dL compared to 13.1 g/dL at baseline) [ 32 ]. However, a study carried out in China found no significant effects in the prevalence of anemia among women who consumed folic acid-fortified wheat flour compared to the control group after 36 months of intervention (RR: 0.87; 95%CI: 0.68, 1.11) [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…One RCT found that six months after the fortification of maize flour, women who consumed the fortified flour had a significant increase in hemoglobin concentrations (mean 13.3 g/dL compared to 13.1 g/dL at baseline) [ 32 ]. However, a study carried out in China found no significant effects in the prevalence of anemia among women who consumed folic acid-fortified wheat flour compared to the control group after 36 months of intervention (RR: 0.87; 95%CI: 0.68, 1.11) [ 56 ].…”
Section: Resultsmentioning
confidence: 99%